Quantificação de cresóis em amostras de fumaça líquida empregando a extração líquido-líquido com purificação em baixa temperatura e análise por cromatografia gasosa-espectrometria de massas - Marina Ranna Pinheiro Vasconcelos (2023)
Liquid smoke is a food additive used to impart a smoky flavor to foods. The three isomers of cresols are among the constituents of liquid smoke, wich are potentially toxic compounds for human health. Thus, the main objective of this study was to optimize a methodology to quantify cresols in liquid smoke. First, the liquid-liquid extraction with low temperature purification (LLE-LTP) technique was optimized and validated for cresols in water, as there are no liquid smoke samples free of cresols. Analyzes were performed by gas chromatography coupled to mass spectrometry (GC-MS) with total ion chromatograms. Subsequently, the LLE-LTP was applied for the extraction of cresols in five commercial samples of liquid smoke and the quantification was performed using the calibration standards in pure solvent and using the standard addition method. The stability of cresols in liquid smoke was also evaluated for 21 days with samples stored under ambient and refrigerated conditions. The proposed methodology proved to be selective for cresols in water, linear in the range of 0.5 to 35 mg L-¹, recovery between 90 and 104% and relative standard deviation (RSD) lower than 10%. The quantification of cresols in four liquid smoke samples showed a strong negative matrix effect and the concentration of cresols ranged from 0.5 to 25 mg L-¹ determined by the standard addition method. The cresol concentration remained constant in the liquid smoke for 21 days at 5 and 25 ºC. Finally, the proposed methodology proved to be adequate for the determination of cresols in liquid smoke and the levels found in the samples are very high.